STRATEGI DAKWAH USTADZ MUSLIM SIREGAR DALAM UPAYA MENINGKATKAN PENGETAHUAN DAN PENGALAMAN IBADAH SHALAT MASYARAKAT DI DESA GUNUNG TUA TAMBU JATI KEC. BATANG ONANG - nur oktari; Khairuddin Khairuddin (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
The primary issue of this exploration is the manner by which the technique utilized by Ustadz Muslim Siregar in Endeavors to Build Information and Practice of Petition for the Local area of Gunung Tua Tumbu Jati Town, Kec. Batang Onang. The reason for the issue in this proposal is to examine the procedure utilized by Ustadz Muslim Siregar With an end goal to Expand Information and Practice of Petition for the Local area of Gunung Tua Tumbu Jati Town, Kec. Batang Onang. The sort of exploration utilized by the creator is field research with an expressive subjective methodology, the information assortment utilized is perception, meetings, and documentation. The consequences of the examination are the Da'wah of Ustadz Muslim Siregar in working on the nature of the request administrations of the Gunung Tua Tumbu Jati people group, specifically by leading recitations where Ustadz Muslim Siregar utilizes 3 da'wah methodologies, in particular: Wistful procedure (Al-manhaj-'athifi) by offering guidance in a delicate way and furthermore persistent, judicious system (Al-Manhaj Al-'Aqli) by giving a gathering to questions and replies to individuals who actually don't figure out the material introduced, tactile technique (Al-manhaj al-'alhissi) by giving models in daily existence, for example, come to the mosque before prior to beginning the request time, welcome the local area to supplicate, discuss dhikr, and implore after petition. Aside from that, Ustadz Muslim Siregar likewise set a genuine model in the public eye. In his da'wah, he contains material for petitioning God administrations, and furthermore legitimizes perusing local area supplications.